Bens fundamentais e razoabilidade prática: contribuição para uma crítica ao conceito de basic values na obra lei natural e direitos naturais de John Finnis - Simões, Edilezia Freire (2023)
Finnis’s philosophy, as a reinterpretation of the tradition of classical thought (mainly Aristotle’s) and Thomasian thought, is structured in a context influenced by the contemporary interpretation that German Grisez makes of the first principle of practical reason presented by Thomas Aquinas, in the Summa theologiae, Ia-IIae, question 94, article 2. In the work Natural law and natural rights, under this influence, Finnis presents the methodology used in the study of his theory of natural law with a reflection on the fundamental goods, of which we highlight practical reasonableness and play. Using the criteria of practical reasonableness, it is possible to identify whether or not a ‘good’ constitutes a ‘central case’; therefore, fundamental for full human flourishing. According to Finnis' theoretical position, there are demands or requirements that basic values need to meet in order for them to be understood as fundamental. As Finnis devotes little attention to the good 'play', this thesis precisely aims to fill this gap by critically deepening the fundamental good play, either from Finnis himself, or based on approaches with other authors in the philosophical tradition. Throughout the thesis, we discuss the methodological assumptions that underlie Finnis's theory of natural law and examine Finnis's theoretical exposition on fundamental goods. In this aspect, we highlight its characteristics and specificities, as well as the criticisms directed at the Finnis’s interpretation regarding the list of fundamental goods, the premorality of these goods and the absence of hierarchy between them, as well as the 'decisionism' presented as a criterion. Finally, once this journey has been completed, it is concluded with a critical contribution to the fundamental good ‘play’ as it is thematized in the work Natural law and natural rights, by John Finnis.